Pollen grain size in four ploidy levels of genus Avena - Katsiotis, Andreas; Forsberg, R. A. (My University, 1995)
Pollen grain size in many genera positively correlated with chromosome number. In this study, oat (Avena) pollen grain size was examined in diploids (2×=14, one species, for accessions), tetraploids (4×=28, five species, 20 accessions), hexaploids (6×=42, one species, eight cultivars), and in 10 octoploid (8×=56) accessions. Mature anthers ready to dehisce pollen were sampled from one to six plants per accession, and pollen grains were squeezed out of the anther with tweezers. Oat pollen grains are slightly elliptical, and the length of the major axis was found to be highly correlated with the minor axis width (r=0.94**). Pollen grain length, 39.3 μm for diploids, 41.3 μm for tetraploids, 47.0 μm for hexaploids, and 48.8 μm for octoploids, was positively correlated (r=0.86**) with ploidy level. No genomic or species effects appeared to influence this trait. Only tetraploid Avena vaviloviana accession PI 412767 produced two distinct class sizes of pollen grains, 99% normal (43.0 μm) and 1% large (52.7 μm).
Keywords: Avena sativa; chromosome number; oat; pollen grain size